Legal Efforts To Prevent And Eradicate Land Mafia - Permatasari, Meta (Inspiring Law Journal, 2024)
Land mafias from time to time always study the actions they take to avoid land disputes with conflicts that in reality always violate the law. One of the things they apply is that the action must be carried out by a group of people in a structured, scheduled and carried out with great care. Land mafias also study how to trick victims who will be their targets later. The position of the Anti-Land Mafia Task Force based on the Technical Instructions of the Directorate General for Handling Agrarian Problems and Utilization of Space and Land Number: 01/JUKNIS/DJ-VII/2018 concerning the Prevention and Eradication of Land Mafia, its position is at 2 (two) different levels, namely first, the ministerial level which is appointed and determined based on the decision of the Minister of ATR/BPN and second, the regional office level, which is determined and appointed based on the decision of the Head of the Provincial BPN Regional Office. The Anti-Land Mafia Task Force only plays a role in implementing research, collection, study and analysis of land case data that are suspected of involving land mafia and can only coordinate it with other agencies and delegate the results of handling land cases that are suspected of involving land mafia to the police